Доказать тождества: a) a²+b²=(a+b)²-2ab б) (a+b)²-4ab=(a+b)² в)(a+b)²+(a-b)²=2(a²+b²) г)(a+b)²-2b(a+b)=a²-b²

dashasviridenko dashasviridenko    2   04.10.2019 00:01    1

Ответы
Юля7071 Юля7071  21.08.2020 21:28

a) a²+b²=(a+b)²-2ab

a²+b²=a²+2ab+b²-2ab

a²+b²=a²+b²

б) (a+b)²-4ab=(a-b)² ???

a²+2ab+b²-4ab=a²-2ab+b²

a²-2ab+b²=a²-2ab+b²

(a-b)²=(a-b)²

в)(a+b)²+(a-b)²=2(a²+b²)

a²+2ab+b²+a²-2ab+b²=2a²+2b²

2a²+2b²=2a²+2b²

г)(a+b)²-2b(a+b)=a²-b²

a²+2ab+b²-2ab-2b²=a²-b²

a²-b²=a²-b²

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра